Protein glycosylation, conserved from yeast to man: a model organism helps elucidate congenital human diseases - Lehle, Ludwig; Strahl, Sabine; Tanner, Widmar (Angewandte Chemie. International edition, 2006)
Proteins can be modified by a large variety of covalently linked saccharides. The present review concentrates on two types, protein N-glycosylation and protein O-mannosylation, which, with only a few exceptions, are evolutionary conserved from yeast to man. They are also distinguished by some special features: The corresponding glycosylation processes start in the endoplasmatic reticulum, are continued in the Golgi apparatus, and require dolichol-activated precursors for the initial biosynthetic steps. With respect to the molecular biology of both types of protein glycosylation, the pathways and the genetic background of the reactions have most successfully been studied with the genetically easy-to-handle baker's yeast, Saccharomyces cerevisae. Many of the severe developmental disturbances in children are related to protein glycosylation, for example, the CDG syndrome (congenital disorders of glycosylation) as well as congenital muscular dystrophies with neuronal-cell-migration defects have been elucidated with the help of yeast.